Comparison of geosat and gravimetric geoid profiles in the North Sea - Stewart, Michael; Featherstone, Will; Kirby, Jonathan (Taylor and Francis, 1998)
Sea surface height profiles derived from 2-year, repeat track, Geosat altimeter data have been compared with a regional gravimetric geoid in the western North Sea, computed using a geopotential model and terrestrial gravity data. The comparison encompasses 18 Geosat profiles covering a 750x850 km area of the North Sea. After a second-order polynomial was used to model the long-wavelength differences which cannot be clearly separated over an area of this size, results show agreement to better than +/-3 cm for wavelengths between approximately 20 and 750 km. In regions where terrestrial gravity data were not available to improve the geoid, similar comparisons with the OSU91A geopotential model alone show differences of up to +/-6 cm. This illustrates the importance of incorporating local gravity data in regional geoid computations, and partly validates the regional gravimetric geoid solution and Geosat sea surface profiles in the western North Sea. It is concluded that, in marine areas where the sea surface topography is known to be small in magnitude, Geosat sea surface profiles can act as an independent control on gravimetric geoids in the medium-wavelength range.